1998
DOI: 10.1128/jvi.72.10.8043-8051.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus Immediate-Early Gene Product, BRLF1, Interacts with the Retinoblastoma Protein during the Viral Lytic Cycle

Abstract: Retinoblastoma protein (Rb) is a key regulator of cellular proliferation, controlling entry into G1/S in the cell cycle, largely through its action in binding the cellular transcription factor E2F, which activates genes important in DNA synthesis. Small DNA tumor viruses encode gene products which can functionally inactivate Rb, promoting cellular proliferation and viral DNA synthesis. In this study, the Epstein-Barr virus (EBV) immediate-early lytic gene product, BRLF1 (R), is shown to bind Rb in vivo, shortl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…This is likely to be the case for at least some tumor viruses during lytic virus replication. EBV, for example, encodes lytic replication transactivator proteins (BRLF1 and BZLF1) which directly inhibit pRB and p53 proteins (45,47). However, pRB inactivation during virus latency does not preferentially replicate viral genome over host cell genome.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be the case for at least some tumor viruses during lytic virus replication. EBV, for example, encodes lytic replication transactivator proteins (BRLF1 and BZLF1) which directly inhibit pRB and p53 proteins (45,47). However, pRB inactivation during virus latency does not preferentially replicate viral genome over host cell genome.…”
Section: Discussionmentioning
confidence: 99%
“…These code for Epstein–Barr nuclear antigen 1 (EBNA1), a latency protein needed for EBV episome replication; EBNA2, a transcription factor that activates EBV latency and immortalizes genes; and lymphocyte membrane‐associated oncoprotein (LMP1), which activates transcription factors, interacts with cell signalling molecules, and may even interfere with p53 mediated apoptosis. The Z protein, which is responsible for initiating the switch from latent to lytic infection, can interact directly in vitro and in vivo with the tumour suppressor protein, p53 [41], whereas the R protein interacts with Rb [42]. EBV is transmitted through saliva and infects epithelial cells of the oropharynx, posterior nasopharynx, parotid gland and duct.…”
Section: Epstein–barr Virus (Ebv)mentioning
confidence: 99%
“…However, it has already been shown that an E2F site is essential for BRLF1 activation of the EBV DNA polymerase (44), suggesting that free cellular E2F is required for replication of viral DNA. Consistent with this model, the level of E2F1 is increased during induction of lytic EBV infection in Akata cells (68). In addition to activating the EBV polymerase, E2F1 induction would be expected to activate the transcription of many proteins involved in cellular DNA synthesis and cell cycle progression.…”
Section: Discussionmentioning
confidence: 67%
“…In herpesviruses, lytic viral replication is associated with a block in cell cycle progression rather than with induction of S phase (2,8,33,45,56). Nevertheless, the immediate-early proteins of both cytomegalovirus (CMV) and EBV inhibit Rb and p53 function (17,47,68,70). In addition, both herpes simplex virus and CMV modulate E2F function(s) (28,48,49).…”
mentioning
confidence: 99%
See 1 more Smart Citation